Giant gallbladder (Revista Argentina de Cirugía, 2021)
We report the case of a 73-year old female patient with a history of chronic cholecystitis with a palpable mass extending from the right hipochondrium to the right iliac region. An abdominal ultrasound showed an enlarged gallbladder extending to the right iliac region with multiple gallstones confirmed by computed tomography scan.An exploratory laparotmy was performed. A giant gallbladder with thickened walls and presence of adhesions to the neighbor organs that were difficult to remove were found and required drainage.A conventional cholecystectomy was performed using the Pribram’s technique. A surgical specimen measuring 15 x 10 cm was sent to the pathologist who made a diagnosis of chronic cholecystitis.This case is an atypical presentation of chronic cholecystitis due to a giant gallbladder.
Keywords: giant gallbladder; chronic cholecystitis; pribram technique; atypical presentation